Perceived Value and Emotional Attachment on Repurchase Intention through Brand Experience - Kusumahadi, Rafaela Abigail; Rodhiah (Journal of Social Science and Business Studies, 2025)
This study aims to analyze the influence of perceived value and emotional attachment on repurchase intention, with brand experience as a mediating variable among consumers of the “XYZ” brand. The research is grounded in the context of intense competition within the Fast-Moving Consumer Goods (FMCG) industry, specifically focusing on the herbal health product category. A quantitative descriptive method was applied using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach through SmartPLS 4. The sampling technique used was non-probability sampling with purposive sampling, distributing a Google Form questionnaire to 156 respondents who are consumers of “XYZ” brand who lives in Jakarta, have already consumed the product at least twice, and intend to buy them again in the future. The results reveal that perceived value and emotional attachment have a positive and significant effect on brand experience and repurchase intention. Brand experience also has a positive and significant effect on repurchase intention and successfully acts as a mediating variable. This study contributes academically to the understanding of consumer behavior and FMCG marketing. The novelty of this research lies in the simultaneous integration of perceived value and emotional attachment, along with the inclusion of brand experience as a mediating variable. In addition, this study explores the herbal health product category within the FMCG sector, which remains limited in existing literature.